1994
DOI: 10.1002/eji.1830241106
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase activity associated with the CD7 antigen: correlation with regulation of T cell integrin function

Abstract: Rapid up-regulation of the functional activity of integrin adhesion receptors is a hallmark of T cell activation. Monoclonal antibody engagement of the CD7 antigen on human T cells results in an increase in beta 1 and beta 2 integrin-mediated adhesion within minutes. This suggests that CD7 is capable of transducing intracellular signals, and is consistent with other indirect studies implicating CD7 as a signaling receptor on T cells. In this report, we have explored the intracellular mechanism by which CD7 mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Although its exact function is unknown, cross-linking of CD7 results in tyrosine kinase-mediated up-regulation of ␤1 and ␤2 integrin expression on T 35 and NK cells, 36 thus modulating adhesion to fibronectin. 37 The ligand for CD7 has not been identified, although a recent report suggested that galectin-1 induced apoptosis in T cells may involve binding to CD7.…”
Section: Discussionmentioning
confidence: 99%
“…Although its exact function is unknown, cross-linking of CD7 results in tyrosine kinase-mediated up-regulation of ␤1 and ␤2 integrin expression on T 35 and NK cells, 36 thus modulating adhesion to fibronectin. 37 The ligand for CD7 has not been identified, although a recent report suggested that galectin-1 induced apoptosis in T cells may involve binding to CD7.…”
Section: Discussionmentioning
confidence: 99%
“…CD7 ϩ T cells may bind galectin-1 expressed by stromal or dendritic cells in tissues where T cells die, such as the thymus during T cell development (19,21) or peripheral lymphoid organs following an immune response (4,20). Galectin-1 may mediate interactions between T cells and stromal cells directly (1,2,8), or galectin-1 may modulate T cell adhesion by cross-linking CD7 on T cells, thereby up-regulating integrin-mediated adhesion (22,23). We have previously demonstrated that 3 Abbreviation used in this paper: [Ca 2ϩ ] i , intracellular calcium concentration.…”
Section: Discussionmentioning
confidence: 99%
“…This effect on adhesion was reduced by treatment with either staurosporine or dibutyryl cAMP, suggesting a role for PKC and cAMP, respectively, in CD7-induced adhesion (142). Further studies have shown that the induction of increased integrin adhesion by CD7 ligation is abolished by pretreatment of the cells with herbimycin A, a tyrosine kinase inhibitor (150). A role for the lipid kinase PI3K in CD7 signaling has been suggested by the observation that the PI3K inhibitors Wortmannin and LY294002 or a dominant negative form of PI3K inhibited CD7-induced integrin adhesion (147).…”
Section: Distribution and Functions Of Cd7mentioning
confidence: 95%
“…This multimeric complex was shown to contain tyrosine kinase activity (144). Independently, CD7 immunoprecipitated from purified CD4 + human T cells was shown to associate with a tyrosine kinase activity (150); the tyrosine phosphorylated band in these immunoprecipitates had a relative molecular weight of 80 kDa, but remains unidentified (150).…”
Section: Structure and Molecular Associations Of Cd7mentioning
confidence: 96%